Vascular patterns provide therapeutic targets in aggressive neuroblastic tumors - Tadeo, Irene (Oncotarget, 2016)
Angiogenesis is essential for tumor growth and metastasis, nevertheless, in NB, results between different studies on angiogenesis have yielded contradictory results. An image analysis tool was developed to characterize the density, size and shape of total blood vessels and vascular segments in 458 primary neuroblastic tumors contained in tissue microarrays. The results were correlated with clinical and biological features of known prognostic value and with risk of progression to establish histological vascular patterns associated with different degrees of malignancy. Total blood vessels were larger, more abundant and more irregularly-shaped in tumors of patients with associated poor prognostic factors than in the favorable cohort. Tumor capillaries were less abundant and sinusoids more abundant in the patient cohort with unfavorable prognostic factors. Additionally, size of post-capillaries & metarterioles as well as higher sinusoid density can be included as predictive factors for survival. These patterns may therefore help to provide more accurate pre-treatment risk stratification, and could provide candidate targets for novel therapies.